Odpowiedzi

2009-11-12T17:10:49+01:00
Wynik: x² -2x + 4
rozwiązanie w załączniku. pozdrawiam:)
2009-11-12T17:32:18+01:00
(x³-6x²+12x-16):(x-4)=x²-2x+4
-X³+4x²
--------------
-2x²+12x
2x²-8x
---------------
4x-16
-4x+16
---------------
=======
Najlepsza Odpowiedź!
2009-11-12T17:33:01+01:00
x² - 2x + 4
-----------------------
x³ - 6x² + 12x - 16 : (x - 4)
-x³ +4x²
-----------------------
-2x² + 12x - 16
+2x² - 8x
-----------------------
4x - 16
-4x + 16
-----------------------
0 0

Rozwiązanie:
(x³ - 6x² + 12x - 16) : (x - 4) = (x² - 2x + 4)